A new genus of the tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae) from China - Meng, Rui; Wang, Yinglun; Qin, Daozheng (Zootaxa, 2013)
A new issid genus in the tribe Hemisphaeriini (Hemiptera: Fulgoromorpha: Issidae) is described from China: Rotundiforma gen. nov.. One new species, Rotundiforma nigrimaculata sp. nov. (China: Yunnan, Menglun), is described and illustrated. Distribution and morphological diversity of tribe Hemisphaeriini are discussed briefly. A checklist for the 14 genera of Hemisphaeriini is provided.